The Eruption of Mount Kelud and It’s Impacts in Blitar 1919-1922 - Ulin Nihayatul; Agustinus Supriyono; Haryono Rinardi (Diponegoro University, 2017)
This study is meant to deal with the aftermaths of Mount Kelud Eruption from 1919 to 1922 in the region of Blitar, which is focused on the effects of Mount Kelud eruption on the economy and its impacts for the three years following the eruption. The aftermaths of Mount Kelud eruption of 1919 had caused many of the residents lose their livelihood, families and damages to the plantations in the region of Blitar. The damages affecting the plantations made the local economy in the region of Blitar drop. This economic slump certainly impeded the development progress in the Gemeente of Blitar, a Gemeente had been formed in the region of Blitar shortly before that. The extensive environmental devastation, inside the gemeente and the outer parts of the regency’s regions forced the regional government of Blitar Regency to allocate aids funds to handle the casualties, make the repairs and constructions of the facilities in the region of Blitar.